High throughput surface mass spectrometry-based proteomics & metabolomics for biological applications - Meurs, Joris (2021)
Surface-based mass spectrometry analysis benefits from the minimum sample preparation required and high throughput nature of the analysis (few minutes per sample) and shows therefore potential for tackling current issues in the field of proteomics and metabolomics. This thesis aims to develop a robust high throughput methodology for the quantitative analysis of surface-adsorbed proteins and for untargeted metabolomics